MASTERING THE ART OF ORAL FLUENCY: A MULTIDIMENSIONAL ANALYSIS OF SECOND LANGUAGE SPEAKING - Tolibjonova Munisa; Xolnazarova Dinara; Poʻlatova Sevinch (Ta’lim innovatsiyasi va integratsiyasi, 2026)
Abstract This article provides a comprehensive and multidimensional exploration into the fundamental dimensions of speaking competence within the framework of second language (L2) acquisition. In the realm of contemporary applied linguistics, achieving oral proficiency is recognized as one of the most complex challenges for learners, involving a sophisticated interplay of cognitive, linguistic, and social factors. This study meticulously examines the intricate balance between the three core pillars of the CAF framework: Complexity, Accuracy, and Fluency. By addressing the cognitive demands imposed on learners during real-time communication, the article analyzes how mental processing constraints impact speech production. Furthermore, the research highlights the critical role of psycholinguistic processing models, specifically Levelt’s model of speech production, and explores how socio-pragmatic adaptation contributes to achieving advanced levels of proficiency. The authors argue that successful L2 speakers do not merely memorize vocabulary, but rather undergo a cognitive transition from controlled, laborious processing to the automatization of speech production through sustained practice and the strategic application of communicative competence. Detailed attention is given to strategic competence— including circumlocution and self-correction—as a vital mechanism for maintaining flow despite linguistic gaps. Additionally, the paper investigates the impact of pragmatic awareness on learner success, emphasizing that near-native proficiency requires an understanding of cultural nuances and register differences. Ultimately, this article aims to synthesize theoretical models with practical implications for both learners and educators, providing a clear pathway toward mastering the art of oral fluency in a second language. The findings suggest that a holistic approach, integrating cognitive development with social awareness, is essential for fostering genuine communicative autonomy in diverse linguistic contexts.